Increased Risk for Group BStreptococcusSepsis in Young Infants Exposed to HIV, Soweto, South Africa, 2004–20081 - Clare Cutland; Stephanie J. Schrag; Michael C. Thigpen; Sithembiso Velaphi; Jeannette Wadula; Peter V. Adrian; Locadiah Kuwanda; Michelle J. Groome; Eckhart Buchmann; Shabir A. Madhi (2015)
Although group B Streptococcus (GBS) is a leading cause of severe invasive disease in young infants worldwide, epidemiologic data and knowledge about risk factors for the disease are lacking from low- to middle-income countries. To determine the epidemiology of invasive GBS disease among young infants in a setting with high maternal HIV infection, we conducted hospital-based surveillance during 2004-2008 in Soweto, South Africa. Overall GBS incidence was 2.72 cases/1,000 live births (1.50 and 1.22, respectively, among infants with early-onset disease [EOD] and late-onset [LOD] disease). Risk for EOD and LOD was higher for HIV-exposed than HIV-unexposed infants. GBS serotypes Ia and III accounted for 84.0% of cases, and 16.9% of infected infants died. We estimate that use of trivalent GBS vaccine (serotypes Ia, Ib, and III) could prevent 2,105 invasive GBS cases and 278 deaths annually among infants in South Africa; therefore, vaccination of all pregnant women in this country should be explored.